Evaluation of Flexor Pollicis Longus Tendon Rupture after Treatment of Distal Radius Fracture with the Volar Plate - Yamak, Kamil; Karahan, Hüseyin Gökhan; Karatan, Berrak; Kayalı, Cemil; Altay, Taşkın (Journal of Wrist Surgery, 2020)
Background The aim of this study is to evaluate the frequency of flexor pollicis longus (FPL) tendon rupture and factors leading to this rupture during the follow-up of patients who underwent volar plate fixation because of distal radius fracture.Patients and Methods A total of 109 distal radius fractures of 102 patients treated with volar plate fixation and periodically followed up for at least 1 year between January 2013 and May 2018 were evaluated. Fractures were categorized according to the AO Foundation/Orthopaedic Trauma Association (AO/OTA) Fracture-Dislocation Classification and Soong's grading was used for classifying volar plate position. All patients operated were inquired retrospectively in terms of flexor tendon rupture.Results Gender distribution revealed 45 females and 57 males. Mean age was 47.9 (range: 17–88) years. Mean period of follow-up was 27 months. Distribution of fractures in accordance with the AO/OTA distal radius classification was 6, 8, 7, 12, 24, 33, 11, and 8 patients with types A2, A3, B1, B2, B3, C1, C2, and C3, respectively. When volar plate positions were analyzed with Soong's classification, it revealed that 79 (72.4%), 23 (21.1%), and 7 (6.5%) plates were grade 0, 1, and 2, respectively. In total, evaluating the three patients with FPL rupture, it revealed that the volar plate was positioned distally during fixation because the fracture line had advanced to the distal of the watershed line, the distal portion of the plate had lost complete connection with the bone, and at this portion, it was observed that the pronator quadratus muscle was not covering the plate entirely (Soong's classification grade 2). Patients did not have additional flexor tendon injury.Conclusion FPL tendon rupture is a rare but serious complication of volar plate fixation performed for distal radius fractures. We believe that appropriate choice of implant and careful surgical technique, along with the close follow-up of patients, with Soong's classification grade-2 volar positions would help in preventing this complication.Level of Evidence This is a Level 3a, differential diagnosis/symptom prevalence study.
Keywords: distal radius fracture; flexor pollicis longus; tendon rupture; volar plate fixation; watershed line